Influence of use of Geographic Information System Media Overlay & Scoring Based to Improve Critical and Creative Thinking Skills in the Implementation of the Independent Curriculum - Putri, Yullia; Pargito; Sugeng Widodo; Risma M Sinaga; Muhammad Mona Adha (International Journal of Educational and Life Sciences, 2023)
This research aims to determine the influence of geographic information system learning media based on overlay and scoring on the ability to think critically and think creatively in geography subjects in the implementation of the 2023/2024 independent curriculum. The research design used in this research is Quasi Experimental with a None-equivalent Control Group Design. The population is all X students, totaling 324 students. From this population, samples were taken, namely class X-5 as the experimental class, totaling 34 students and class The sampling technique uses the Purposive Sampling Technique, namely sampling based on certain considerations. The research results obtained from class X-5 as an experimental class had an average posttest score of 76.62. Meanwhile, in class X-6 as the control class the average posttest value was 71.47. The hypothesis test results obtained were sig. (2-tailed) 0.000. So a value of 0.000 < 0.05 means that H1 is accepted and Ho is rejected. So it can be concluded that there is an influence of overlay and scoring based Geographic Information System Learning Media on the ability to think critically and think creatively in class X-5 SMA Al Kautsar even semester of the 2023/2024 academic year.